The Eophreatoicus Nicholls, 1926 species flock from Kakadu and Arnhem Land, with a description of a new genus of Amphisopidae (Crustacea : Isopoda : Phreatoicidea) - Wilson, George D.f.; Humphrey, Christopher L. (Zootaxa, 2020)
We present descriptions of 28 new species of Amphisopidae from Arnhem Land and Kakadu National Park of Australia’s Northern Territory. We identified five additional species that are not yet fully characterized and are not provided with formal species recognition. This is the first taxonomic treatment highlighting the high species richness within the Phreatoicidea that occur in Australia and likely elsewhere. We document each species fully with scanning electron and light micrographic images, diagnoses, detailed descriptions, keys to identification and justification of each species using parsimony analysis of their morphological and genetic characters. The distributional data show that all species, except for one, have microendemic distributions, with some sibling species occurring within a few kilometers of each other. Because of the age of this group of species, they appear to have spread throughout the region of the Arnhem sandstone plateau and then back-colonized the same habitats so that as many as three morphologically and genetically distinct species may co-occur syntopically. Our research has uncovered a new genus-level taxon of the family Amphisopidae, Kakadubeh gen. nov. This new genus is unlike Eophreatoicus, not only in its general appearance, but also in having an inferred reproductive strategy different from most of the other members of the family. While Eophreatoicus species have males that are much larger than the females and practice precopula, a form of pre-insemination mate guarding, males of the new species, Kakadubeh rangemyahwurd sp. nov., are much smaller than females. In addition, males of this species have a fourth walking leg that is not specialized for holding females, suggesting that they have a reproductive strategy that does not involve precopula of the form seen in Eophreatoicus and Eremisopus Wilson & Keable, 2002a. Most of our research has been undertaken in Kakadu National Park, although recent collections have been made in Arnhem Land, yielding additional distinctive species. Given the size of unexplored territory around the Arnhem Plateau and the geographic frequency of discovering new species, we predict that the diversity of this group in the Northern Territory may be many more than the ~35 species described here. At this time, these microendemic isopods appear to be unthreatened by human activities, largely owing to the environmental protection afforded by Kakadu National Park and Arnhem Land, and their cryptic habits during the dry season. Because they are dependent on small springs of permanent groundwater, future changes in hydrology owing to water use and climate change, as well as invasive introduced species, may present risks to populations and species.